Applicability of the Hoek-Brown failure criterion and the effect of the anisotropy on intact rock samples from “Athens Schist” - H. Saroglou; P. Marinos; G. Tsiambaos (The Southern African Institute of Mining and Metallurgy, 2003)
The anisotropic behaviour of “Athens Schist” has been brought out through the testing of specimens with varying orientation of schistosity with respect to the major principal stress under uniaxial, triaxial and dynamic conditions. A large number of results from tests on intact rock specimens of the “Athens Schist” were statistically analysed and evaluated. Le comportement anisotropique des roches du système “Schistes d’ Athènes” a été déterminé sur des épreuves avec une orientation différente de la schistosité par rapport à l’axe de chargement sous des conditions axiales, triaxiales et dynamiques. Un grand nombre des résultats a été statistiquement analysé et discuté. Zur Bestimmung der anisotropen Eigenschaften der Athen Schiefer wurden einaxialen, dreiaxialen und dynamischen Kompressionsversuchen an Gesteinskernen durchgeführt, bei denen die Belastungsachse verschiedenen Neigungen gegen die Schieferung hat. Die Messreihen an anisotropen unzerreissbaren Fels Samplen von Athen Schiefer wurden statistisch analysiert.